Hippocampal Neurogenesis and the Brain Repair Response to Brief Stereotaxic Insertion of a Microneedle - Shijie Song; Shuojing Song; Chuanhai Cao; Xiaoyang Lin; Kunyu Li; Vasyl Sava; Juan Sanchez-Ramos (Stem Cells International)
We tested the hypothesis that transient microinjury to the brain elicits cellular and humoral responses that stimulate hippocampal neurogenesis. Brief stereotaxic insertion and removal of a microneedle into the right hippocampus resulted in (a) significantly increased expression of granulocyte-colony stimulating factor (G-CSF), the chemokine MIP-1a, and the proinflammatory cytokine IL12p40; (b) pronounced activation of microglia and astrocytes; and (c) increase in hippocampal neurogenesis. This study describes immediate and early humoral and cellular mechanisms of the brain’s response to microinjury that will be useful for the investigation of potential neuroprotective and deleterious effects of deep brain stimulation in various neuropsychiatric disorders.